Period Doubling of Dissipative-Soliton-Resonance Pulses in Passively Mode-Locked Fiber Lasers - Du, Wenxiong; Li, Heping; Lyu, Yanjia; Wei, Chen; Liu, Yong (Frontiers in Physics, 2020)
Period-doubled dissipative-soliton-resonance (DSR) pulses are numerically investigated in a Yb-doped fiber laser based on nonlinear amplifying loop mirror (NALM). In the case of low pump power, stationary dissipative solitons with uniform pulse peak power are obtained in the laser. Further increasing the pump power, the laser operates in the DSR regime, where the phenomenon of period-doubling bifurcations could occur. In a period-doubled state, the pulse peak power returns back to its original one every two cavity roundtrips while the pulse duration remains almost the same. We analyze the effects of cavity parameters on the DSR-pulse features under the dynamic bifurcations. It is found that the saturation power of NALM plays a dominant role in the formation of period-doubled DSR pulses. Our simulation results are conducive to enriching the dynamics of DSR pulses in nonlinear systems.